HONEY TRADE IN BULGARIA AND ITS IMPACT ON THE APPICULTURAL SECTOR - G. Aleksiev (Trakia Journal of Sciences)
Bulgarian apiculture undergoes a process of consolidation and concentration of production. Small producers have played an increasingly insignificant role over the last few years, and this has led to changes in trade with the industry's main product - honey. The purpose of this study is to analyze trade flows of honey from and to Bulgaria as a basis for the development of trade in the sector and its future sustainable development. In order to achieve its goal, the research should address the following tasks: to study the structure and sources of honey imports in the country; to analyze exports and trends; to assess the impact of trade flows on production in the sector.